The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1530/erc-12-0183
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of miRNA and mRNA expression profiles in pheochromocytoma and paraganglioma identifies genotype-specific markers and potentially regulated pathways

Abstract: Pheochromocytomas (PCCs) and paragangliomas (PGLs) are rare neuroendocrine neoplasias of neural crest origin that can be part of several inherited syndromes. Although their mRNA profiles are known to depend on genetic background, a number of questions related to tumor biology and clinical behavior remain unanswered. As microRNAs (miRNAs) are key players in the modulation of gene expression, their comprehensive analysis could resolve some of these issues. Through characterization of miRNA profiles in 69 frozen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 72 publications
4
59
0
Order By: Relevance
“…Recently, de Cubas et al leveraged miRNA expression profiles to demonstrate that miR-137 and miR-382 were globally upregulated in all paragangliomas with the exception of MAX-related tumors, whereas miR-96, miR-183, and miR-210 were specifically upregulated in SDHB-related tumors. 30 While the exact mechanism by which miRNA aberrations contribute to paraganglioma formation in genetically predisposed individuals remains unclear, initial mRNA profiling data suggest that miRNA-mediated mRNA degradation results in a reduction in neuronal and neuroendocrine-associated development pathways. 30 Future studies in this area may leverage advances in RNA sequencing technologies to decipher the exact role of miRNA and mRNA in familial and sporadic paraganglioma tumorigenesis.…”
Section: Expression Of Mirna and Mrnamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, de Cubas et al leveraged miRNA expression profiles to demonstrate that miR-137 and miR-382 were globally upregulated in all paragangliomas with the exception of MAX-related tumors, whereas miR-96, miR-183, and miR-210 were specifically upregulated in SDHB-related tumors. 30 While the exact mechanism by which miRNA aberrations contribute to paraganglioma formation in genetically predisposed individuals remains unclear, initial mRNA profiling data suggest that miRNA-mediated mRNA degradation results in a reduction in neuronal and neuroendocrine-associated development pathways. 30 Future studies in this area may leverage advances in RNA sequencing technologies to decipher the exact role of miRNA and mRNA in familial and sporadic paraganglioma tumorigenesis.…”
Section: Expression Of Mirna and Mrnamentioning
confidence: 99%
“…30 While the exact mechanism by which miRNA aberrations contribute to paraganglioma formation in genetically predisposed individuals remains unclear, initial mRNA profiling data suggest that miRNA-mediated mRNA degradation results in a reduction in neuronal and neuroendocrine-associated development pathways. 30 Future studies in this area may leverage advances in RNA sequencing technologies to decipher the exact role of miRNA and mRNA in familial and sporadic paraganglioma tumorigenesis.…”
Section: Expression Of Mirna and Mrnamentioning
confidence: 99%
“…Extensive clinical and genetic characterization over the last 25 years has greatly improved our knowledge about the genetic basis underlying PPGLs. Fortunately, application of high-throughput technologies to study PPGL has enhanced our understanding of tumor biology and has already led to novel therapeutic strategies, which may soon be applied in routine clinical practice (3)(4)(5)(6)(7). However, lack of reliable markers for metastatic disease and/or their limited predictive value continue to complicate the clinical management of patients with PPGL.…”
Section: Introductionmentioning
confidence: 99%
“…Previous cytogenetic, transcriptomic, and miRNA expression performed in PPGL have shed light on some of the molecular events underlying these tumors (3,4). Notwithstanding, the epigenetic landscape in PPGL has just only recently been explored (2,8).…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic tumors are represented in both clusters instead of forming clusters of their own, indicating that similar molecular mechanisms are involved. A recent study showed that expression profiling of microRNAs (which are small non-coding RNA molecules with important roles in modulating gene expression 144 ), also successfully classifies pheochromocytomas and paragangliomas into one VHL/SDHx cluster and one RET/NF1/TMEM127/MAX cluster 145 .…”
Section: Hormone Profiles Gene Expression and Epigeneticsmentioning
confidence: 99%